Comparative study of respiratory muscle strength in women undergoing conventional and single-port laparoscopic cholecystectomy - Borges,Marisa de Carvalho (2017)
Abstract Purpose: To evaluate respiratory muscle strength (PImax and PEmax) before and 24 and 48 h after conventional and single-port laparoscopic cholecystectomy. Methods: Forty women with symptomatic cholelithiasis (18 to 70 years) participated in the study. The patients were divided into two groups: 21 patients undergoing conventional laparoscopic cholecystectomy and 19 patients undergoing single-port laparoscopic cholecystectomy. Differences were considered to be significant when p<0.05. Results: The results showed a greater decline in PImax after 24 h in the group submitted to conventional laparoscopic cholecystectomy, with a significant difference between groups (p=0.0308). Conclusion: Recovery of the parameters studied was more satisfactory and respiratory muscle strength was less compromised in the group submitted to single-port laparoscopic cholecystectomy.